AGRIBUSINESS DEVELOPMENT STRATEGY OF PADDY IN SUNGAI MANDAU SIAK DISTRICT - Syaiful Hadi; Deby Kurnia; Wahyu Saputra (Indonesian Journal of Agricultural Economics, 2018)
This study aimed to analyze the agribusiness of paddy and formulate the development of paddy agribusiness in Sungai Mandau. The primary data obtained by directly interviewing the paddy farmerswith the help of the research questionnaire and data used are secondary data from the related offices in Sungai Mandau, the data used is the primary data of the planting season in 2016. The analysis method used is descriptive analysis method, farming analysis, marketing analysis, and SWOT analysis.The results of the research show thatthe subsystem of procurement and distribution of production facilities including seeds, fertilizers, pesticides, and farming equipment is appropriate, which is on time, quantity, place, quality, type, and price. Average production of GKG in the research location is still low compared to production standard but it is feasible to be developed and provide benefits for farmers. The process of drying the Harvest Wet Grain (GBP) into Dried Milled Grain (GKG) by farmers is still conducted manually or using sun-drying method. The amount of marketing margin is IDR 5000,-/ Kg with efficiency of marketing channel is considered efficient. Supporting institution is still not functioning optimally. Alternative of Rice Wetland Agribusiness Development Strategy in Sungai Mandauinclude encouraging farmers to do IP 300, revitalization of Production Facility and Infrastructure, and extension in the paddy field farming program.